2012
DOI: 10.1002/jcu.22005
|View full text |Cite
|
Sign up to set email alerts
|

Ascites, hydrocolpos, hydrometrocolpos with normal amniotic fluid in a fetus with partial urorectal septum malformation sequence

Abstract: Urorectal septum malformation sequence (URSMS) describes a range of anatomic anomalies in the urogenital and lower gastrointestinal organs caused by incomplete urorectal membrane septation and persistence of the cloacal membrane. Partial URSMS is a milder version characterized by a single perineal opening. We report a case of partial URSMS that associated an intact Mullerian system, single perineal opening, blind colon, imperforate anus and vagina, urethrovaginal connection, and ambiguous genitalia. Hydrocolpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Some of this fluid was also likely released intra-abdominally via the Mullerian structures leading to fetal ascites. Warne et al [2] reported one case of partial/persistent cloacal malformation with fetal ascites and normal AFI, but they did not demonstrate initial anhydramnios and progression to normal amniotic fluid level [11].…”
Section: Discussionmentioning
confidence: 99%
“…Some of this fluid was also likely released intra-abdominally via the Mullerian structures leading to fetal ascites. Warne et al [2] reported one case of partial/persistent cloacal malformation with fetal ascites and normal AFI, but they did not demonstrate initial anhydramnios and progression to normal amniotic fluid level [11].…”
Section: Discussionmentioning
confidence: 99%
“…Escobar et al [ used the name, urorectal septum malformation sequence (URSMS), to explain a rare, often lethal condition due to abnormal partitioning of the cloaca. Many examples are now published, including individuals with partial forms and a child treated in utero by vesico‐amniotic shunting [Wheeler et al, ; Wheeler and Weaver, ; Lubusky et al, ; Kanamori et al, ; Lee et al, ].…”
Section: Introductionmentioning
confidence: 99%